Someone else's shoes : a novel - Moyes, Jojo, 1969-; OverDrive, Inc. (New York : Pamela Dorman Books / Viking, 2023)
"A story of mix-ups, mess-ups and making the most of second chances, this is the new novel from #1 New York Times bestselling author Jojo Moyes, author of Me Before You and The Giver of Stars Who are you when you are forced to walk in someone else's shoes? Nisha Cantor and Sam Kemp are two very different women. Nisha, 45, lives the globetrotting life of the seriously wealthy, until her husband inexplicably cuts her off entirely. She doesn't even have the shoes she was, until a moment ago, standing in. That's because Sam - 47, middle-aged, struggling to keep herself and her family afloat - has accidentally taken Nisha's gym bag. Now Nisha's got nothing. And Sam's walking tall with shoes that catch eyes - and give her a career an unexpected boost. Except Nisha wants her life back - and she'll start with her shoes . . . Someone Else's Shoes is a funny, moving and heartfelt story about how, for any of us just one little thing can suddenly change everything"--
Electronic book.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Electronic books